Differences in the Effect of Active Recovery Post Long Duration Interval Training towards Lactate in Young Men with Blood Type O and A - Bangsa, Yohanes de la Cruz Gilang Putra; Arhab, Abiyyu Bari (Universitas Negeri Semarang, 2022)
Accumulation of lactate in the blood can cause fatigue and decreased physical performance. Therefore, proper recovery after physical activity is needed. This study aims to determine the effect of long duration interval training (LDIT) and active recovery on blood lactate and to determine the difference in the decrease in lactate levels between blood groups O and A after active recovery. This research is included in comparative research. The independent variable in this study was active recovery, and the dependent variable in this study was blood lactate levels (mmol/L). The sample in this study was taken from the NFC Academy which has a population of 35 members. Sampling was done by purposive randomized sampling, and obtained 16 members who are declared eligible and willing to be the research sample. Then the sample was given LDIT physical activity and active recovery. Data analysis used the T-Test difference test with the help of SPSS 25 software. The results in this study showed a significant increase in blood lactate levels after doing LDIT exercise. After performing active recovery, lactate levels from both groups decreased significantly. It can be said that the two groups had no difference in the effect of active recovery after doing physical activity.